Bat Influenza M2 Shows Functions Similar to Those of Classical Influenza A Viruses - Wenyu Yang; Liping Wang; Lei Shi; Jialin Zhang; Heidi Liu; Jun Wang; Wenjun Ma (Pathogens)
Novel bat influenza viruses show different features in contrast to classical influenza A viruses (IAVs). The M2 of IAVs functions as an ion channel that plays an important role in virus entry, viral assembly, and release and also serves as the antiviral target. To date, whether bat influenza M2 functions as the ion channel like classical IAV M2 remains unknown. Here, we show that the bat influenza M2 amino acid at position 31 (N/S) is critical for sensitivity to antivirals targeting the ion channel such as amantadine and other tested antivirals and that the amino acids at position 37 (H/G) and 41 (W/A) are crucial for virus replication and survival. The results indicate that bat influenza M2 functions similarly to conventional IAVs despite the low identity between the two.